Sosial Emosional Anak Usia 0-6 Tahun dan Stimulasinya Menurut Teori Perkembangan - Ulya Ainur Rofi’ah; Nurlaili Dina Hafni; Layyinatul Mursyidah (Az-Zahra: Journal of Gender and Family Studies, 2022)
The purpose of this study was to describe the stages of social emotional development of children aged up to six years old and their stimulation from a developmental psychology perspective. The research design used is qualitative with a choice of literature study methods. Socio-emotional development is one aspect of development that is very important for every child because it is one of the determinants of his success in the future. In understanding the socio-emotional development of children aged 0-6 years, it can be seen by children from infancy and will develop rapidly when they are toddlers. Parents are responsible for educating and nurturing their children so that they become good people in their adult years. Thus, to form a good personality, preschool children need parenting in accordance with the child's characteristics, so that in educating their children they will get good social and emotional development. So that if children get the right stimulation from their immediate environment (family), especially parents, the child's social emotional development will be able to develop optimally. However, if the child does not get the stimulation that the child should get from an early age, then it will become an obstacle to the child's development.